2008
DOI: 10.1080/13547500802054611
|View full text |Cite
|
Sign up to set email alerts
|

Validation of biomarkers for the study of environmental carcinogens: a review

Abstract: There is a need for validation of biomarkers. Our aim is to review published work on the validation of selected biomarkers: bulky DNA adducts, N-nitroso compounds, 1-hydroxypyrene, and oxidative damage to DNA. A systematic literature search in PubMed was performed. Information on the variability and reliability of the laboratory tests used for biomarkers measurements was collected. For the evaluation of the evidence on validation we referred to the ACCE criteria. Little is known about intraindividual variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 138 publications
1
25
0
Order By: Relevance
“…Variability is a typical characteristic of biological systems, reported by various authors when using the comet and micronucleus assay as well as other cytogenetic endpoints [21,25,27,29,39,40]. Variances that were recorded in baseline DNA damage measured by the comet assay and the frequency of MN, NPBs and NBUDs in our study could be in part attributed to individual genome sensitivity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Variability is a typical characteristic of biological systems, reported by various authors when using the comet and micronucleus assay as well as other cytogenetic endpoints [21,25,27,29,39,40]. Variances that were recorded in baseline DNA damage measured by the comet assay and the frequency of MN, NPBs and NBUDs in our study could be in part attributed to individual genome sensitivity.…”
Section: Discussionmentioning
confidence: 84%
“…Genetic susceptibility and environmental exposures during vulnerable periods of development are also important contributors to the etiology of many childhood diseases [18,19]. Among the adverse health effects that could be studied in children exposed to various environmental hazards, cytogenetic damage received special attention after it had been shown that a high frequency of DNA/chromosome damage is predictive of cancer in healthy adults [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, further standardization of the assay needs to be performed to control for interlaboratory variations. Currently, in the genotoxicity community, there is a large push to establish standardized techniques, establish reference values and internal standards, and standardize statistical analyses for the assay (45)(46)(47). Overall, the high sensitivity of measuring DNA strand breaks by comet assay may complement the poor sensitivity of plasma zinc concentrations, help to identify individuals with marginal zinc deficiency, and test the effectiveness of treatments.…”
Section: Tablementioning
confidence: 99%
“…Those biomarkers specific for PAHs include urinary 1-hydroxypyrene and the measurement of PAH-protein and DNA adducts by immunoassay, while the 32 Ppostlabelling assay for DNA adducts is more sensitive, but less specific. Overall, different biomarkers have been validated to varying extents (Gallo et al, 2008). Measurement of cytogenetic damage, including chromosomal aberrations, is not particularly sensitive for measuring environmental PAH exposure.…”
Section: Rationalementioning
confidence: 99%